2009
DOI: 10.1007/s11999-009-0904-9
|View full text |Cite
|
Sign up to set email alerts
|

Alumina-on-alumina Total Hip Arthroplasty in Young Patients: Diagnosis is More Important than Age

Abstract: Total hip arthroplasty (THA) in young patients has a high loosening rate, due in part to acetabular deformities that may compromise bone fixation and polyethylene wear. We therefore asked whether wear or osteolysis and loosening differ in patients under 40 years of age with alumina-on-alumina THA compared to those who are older. We prospectively followed 56 patients (63 hips) younger than 40 years (Group 1) and 247 patients (274 hips) older than 40 (Group 2) who had an alumina-on-alumina THA. The minimum follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 38 publications
3
20
0
3
Order By: Relevance
“…Some authors have suggested that higher rates of failures in the patients younger than 20 years were more likely attributable to the underlying cause of hip dysfunction rather than young age, especially in the case of developmental dysplasia and inflammatory arthritis [17]. In our study, the underlying diagnosis was mainly chemotherapy or steroid-induced osteonecrosis in 56% of the hips.…”
Section: Discussionmentioning
confidence: 51%
“…Some authors have suggested that higher rates of failures in the patients younger than 20 years were more likely attributable to the underlying cause of hip dysfunction rather than young age, especially in the case of developmental dysplasia and inflammatory arthritis [17]. In our study, the underlying diagnosis was mainly chemotherapy or steroid-induced osteonecrosis in 56% of the hips.…”
Section: Discussionmentioning
confidence: 51%
“…Among modifiable risk factors, multiple factors such as high activity level [3,14,17,30,43,44,48], obesity [2,9,10,34,37,38,43,46,48,51,52], and smoking [10,12,16,17,19,32,35,41] may be associated with an increase in the risk of aseptic loosening after THA.…”
Section: Discussionmentioning
confidence: 99%
“…Alumina-on-alumina bearings, which exhibit little wear, were introduced as an option for young patients [11,30]. These bearings are characterized by low surface roughness, high hardness for major scratch resistance, and high wettability [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports describe alumina-on-alumina bearings used in THAs in young patients [1,3,19,30], and report survivorship ranging from 91% to 99% at 7 to 11 years [10,11,21,24]. We previously reported 5-year followup results of patients younger than 40 years [38], and 10-year followup results in a series of 100 patients [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation